Genetic diversity and kelp forest vulnerability to climatic stress - Wernberg, T.; Coleman, M.; Bennett, Scott; Thomsen, M.; Tuya, F.; Kelaher, B. (Nature Publishing Group, 2018)
© 2018 The Author(s). Genetic diversity confers adaptive capacity to populations under changing conditions but its role in mediating impacts of climate change remains unresolved for most ecosystems. This lack of knowledge is particularly acute for foundation species, where impacts may cascade throughout entire ecosystems. We combined population genetics with eco-physiological and ecological field experiments to explore relationships among latitudinal patterns in genetic diversity, physiology and resilience of a kelp ecosystem to climate stress. A subsequent 'natural experiment' illustrated the possible influence of latitudinal patterns of genetic diversity on ecosystem vulnerability to an extreme climatic perturbation (marine heatwave). There were strong relationships between physiological versatility, ecological resilience and genetic diversity of kelp forests across latitudes, and genetic diversity consistently outperformed other explanatory variables in contributing to the response of kelp forests to the marine heatwave. Population performance and vulnerability to a severe climatic event were thus strongly related to latitudinal patterns in genetic diversity, with the heatwave extirpating forests with low genetic diversity. Where foundation species control ecological structure and function, impacts of climatic stress can cascade through the ecosystem and, consequently, genetic diversity could contribute to ecosystem vulnerability to climate change.